Particle Size Effects on Limestone Channel Treatment of Acid Mine Drainage - Qurniawan, Ridho; Dwifajar Prabowo, Jerry; Nurrochman, Andrieanto (ETHOS: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2026)
Acid mine drainage (AMD) is acidic wastewater from mining activities containing dissolved heavy metals, posing serious environmental threats if discharged without treatment. Despite various passive treatment technologies, the relationship between limestone particle size and physicochemical parameters in Open Limestone Channel (OLC) systems remains insufficiently understood, particularly regarding the trade-off between short-term reactivity and long-term armoring susceptibility. This study aimed to simulate and evaluate OLC performance in neutralizing synthetic AMD (FeSO₄ solution; pH 0.99; Fe³⁺ = 10 mg/L) using Padalarang limestone in three particle sizes (#10, #12, and #16 mesh). The novelty lies in the integrated evaluation of pH, ORP, TDS, and EC alongside direct visual observation of armoring formation under controlled laboratory conditions. Results showed that #10 mesh achieved the highest average pH of 7.15 (range: 6.64–7.68), while #16 mesh exhibited faster passivation and more intensive armoring despite higher initial reactivity. All channels reduced ORP from 557 mV to ~135–145 mV and decreased TDS, while EC increased due to Ca²⁺ and HCO₃⁻ ion release. Appropriate particle size selection is critical to optimizing reactivity and durability in OLC-based passive AMD treatment.